Optimal Approximate Solutions of Fixed Point Equations - S. Sadiq Basha; N. Shahzad; R. Jeyaraj (Abstract and Applied Analysis)
The main objective of this paper is to present some best proximity point theorems for K-cyclic mappings and C-cyclic mappings in the frameworks of metric spaces and uniformly convex Banach spaces, thereby furnishing an optimal approximate solution to the equations of the form 𝑇𝑥=𝑥 where 𝑇 is a non-self mapping.